2019
DOI: 10.3390/pharmaceutics11020062
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting, Antinociceptive Effects of pH-Sensitive Niosomes Loaded with Ibuprofen in Acute and Chronic Models of Pain

Abstract: Ibuprofen is one of the non-steroidal anti-inflammatory drugs (NSAIDs) widely used to treat pain conditions. NSAIDs encounter several obstacles to passing across biological membranes. To overcome these constraints, we decided to study the effects of a new pH-sensitive formulation of niosomes containing Polysorbate 20 derivatized by Glycine and loaded with ibuprofen (NioIbu) in several animal models of pain in mice. We performed two tests commonly used to study acute antinociceptive activity, namely the writhin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…There are several reports on the anti-inflammatory activity of niosomes or proniosomes and their pharmacological effects [29,63,64]. Akbari et al studied the anti-inflammatory effect of curcumin loaded niosomes and revealed a higher anti-inflammatory and antinociceptive activity of the curcumin niosome formulation in the formalin test [29].…”
Section: Formalin Testmentioning
confidence: 99%
“…There are several reports on the anti-inflammatory activity of niosomes or proniosomes and their pharmacological effects [29,63,64]. Akbari et al studied the anti-inflammatory effect of curcumin loaded niosomes and revealed a higher anti-inflammatory and antinociceptive activity of the curcumin niosome formulation in the formalin test [29].…”
Section: Formalin Testmentioning
confidence: 99%
“…IBU, a typical nonsteroidal anti-inflammatory drug, is broadly exploited to treat pain, fever and inflammation. However, its poor water solubility always limits its fast action for achieving a desired therapeutic effect [46,47,48]. HPMC is commonly utilized as an excipient in oral tablet, eye drops, and capsule formations.…”
Section: Introductionmentioning
confidence: 99%
“…The concept relies on preparing drug-loaded niosomes with pH-sensitive molecules added to the formulation; the niosomes are stable under physiological conditions but undergo structural changes when exposed to pathological conditions [ 81 , 82 ]. These niosomes comprise non-ionic surfactants and cholesterol as basic components; pH sensitivity is achieved through adding molecules such as peptides [ 83 ], derivatized lipids [ 84 , 85 ], derivatized surfactants [ 86 ] and pH-sensitive polymers [ 87 , 88 ].…”
Section: Specialised Niosomesmentioning
confidence: 99%